2005
DOI: 10.1007/s00420-005-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Negative association between serum dioxin level and oxidative DNA damage markers in municipal waste incinerator workers

Abstract: With respect to the subjects' serum dioxin level, dioxin did not increase the urinary 8-OH-dG level by oxidative DNA damage, but upregulation of the primary defenses with oxidative damage and/or DNA repair system activity might have occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…However, studies concerning internal exposure of workers employed in these facilities are rather scarce. In addition, most of these studies have been carried out in workers at municipal waste incinerators (Hours et al 2003;Leem et al 2003;Kumagai et al 2004;Hu et al 2004;Charbotel et al 2005;Kim et al 2005a;Shih et al 2006b;Yoshida et al 2006), and excepting a survey performed in Germany, in which the levels of a number of metals and organic substances (PCBs, HCB, CLPs, 1-HP, BTEX) were biologically monitored (Angerer et al 1992), the remaining studies were mainly focused on determining PCDD/F concentrations in blood (Kumagai and Koda 2005;Moon et al 2005;Shih et al 2006a, b). Studies concerning the internal exposure of workers at industrial or hazardous waste incinerators are particularly scarce.…”
Section: Discussionmentioning
confidence: 98%
“…However, studies concerning internal exposure of workers employed in these facilities are rather scarce. In addition, most of these studies have been carried out in workers at municipal waste incinerators (Hours et al 2003;Leem et al 2003;Kumagai et al 2004;Hu et al 2004;Charbotel et al 2005;Kim et al 2005a;Shih et al 2006b;Yoshida et al 2006), and excepting a survey performed in Germany, in which the levels of a number of metals and organic substances (PCBs, HCB, CLPs, 1-HP, BTEX) were biologically monitored (Angerer et al 1992), the remaining studies were mainly focused on determining PCDD/F concentrations in blood (Kumagai and Koda 2005;Moon et al 2005;Shih et al 2006a, b). Studies concerning the internal exposure of workers at industrial or hazardous waste incinerators are particularly scarce.…”
Section: Discussionmentioning
confidence: 98%
“…Thirty‐six papers 15,22,27–60 investigated exposure to waste incinerator emissions by measurement of body substances. Upon review, five were found to have been misclassified and were excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The author points out that although the 1,2,3,4,6,7,8-HpCDF marker had an average level six times above that of the general population, this had no significant effect on the total Toxic Equivalent (TEQ) of exposed subjects whose results were compatible with the average levels of the population. A more significant effect is observed in relation to cigarette smoke than for dioxins in terms of oxidation damage of DNA (Yoshida et al, 2006).…”
Section: Human Biomonitoring and Evaluation Of Occupational Exposurementioning
confidence: 88%
“…It emerges that both the concentration of dioxin in the serum and the total TEQ are comparable in workers and residents in the vicinity of incinerators (Hu et al, 2004;Yoshida et al, 2006) or inferior in workers (Kim et al, 2005;Moon et al, 2005). Higher levels of contamination can be noticed using hair of workers as indicator compared to the general population (Nakao et al 2005).…”
Section: Dioxinsmentioning
confidence: 96%
See 1 more Smart Citation